Elevated pCO2 leading to Late Triassic extinction, persistent photic zone euxinia, and rising sea levels - Jaraula, Caroline; Grice, Kliti; Twitchett, R.; Bottcher, M; Le Metayer, P.; Dastidar, A.; Opazo, L. (Geological Society of America, 2013)
The Late Triassic mass extinction event is the most severe global warming–related crisis to have affected important extant marine groups such as scleractinian corals, and offers potential insights into climate change scenarios. Here we present evidence from Chlorobi-derived biomarkers of episodic and persistent photic zone euxinia. From biomarkers and stable carbon isotopes, we present evidence of rapid mixing of atmospheric and oceanic carbon reservoirs. Global versus regional trends are resolved in kerogen organic matter type, carbonate 13C, and bulk and pyrite 34S. This suite of data demonstrates for the fi rst time a comprehensive organic and stable isotope geochemical reconstruction of events leading up to the Late Triassic extinction event and its aftermath. The cascade of events prior to, during, and after the extinction is remarkably similar to those reported for the Late Permian extinction, the largest extinction event of the Phanerozoic. We predict that similar conditions will have occurred during all past episodes of rapid global warming and biotic crisis that are associated with similar rises in pCO2.